Physico-chemical and mechanical characterization of hydraulic mortars containing cissus glauca roxb as a bio - admixture for restoration applications - Ravi, R.; Sekar, S. K.; Bhuvaneshwari, B.; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
The use of lime mortar expands several millennia ago and was cited in the architectural feats of all kinds of civilizations. Besides the basic ingredients of hydraulic lime, sand and water, organic admixtures were also added to mortars to modify fresh and hardened state properties as well as its durability. The motivation of the present work is to propose a methodology for the natural replacement of synthetic admixtures by bio-admixtures as repair mortar towards protection of heritage structures. Knowing the use of Cissus glauca Roxb (CGR) in historical mortars, used in ancient temples and monuments in Kerala, it is proposed to give a technical insight to repair the mortar. Moreover, addition of CGR extract is expected to increase the durability of lime-based mortars used for repair. In the present study, the effect of CGR extract on the properties of lime-based mortars is studied. Mortar´s composition is selected with respect to the composition of historic mortars and modern restoration practice. Based on the pilot study CGR extract is added in two different concentrations 15% and 20% by the weight of binder. The consistency of modified mortars, mechanical behavior, water absorption, porosity and water/salt absorption through capillary rise have been measured. Chemical–physical properties of the resulting mortars have been evaluated by X-ray diffraction (XRD), and Fourier Transform- Infrared Spectroscopy (FT-IR) to identify their mineralogical composition and morphology by electron microscopy (SEM-ED AX). It is observed that addition of 15% CGR extract produced maximum positive effect on the strength and durability of lime mortars. It improves the mechanical characteristics and limits water and salt absorption by capillarity into mortar through its hydrophobic nature.